Effect of Diets on Plasma and Aorta Lipidome: A Study in the apoE Knockout Mouse Model. Issue 2 (5th December 2022) - Busnelli, Marco; Manzini, Stefano; Colombo, Alice; Franchi, Elsa; Lääperi, Mitja; Laaksonen, Reijo; Chiesa, Giulia
Abstract : Scope: Specific lipid molecules circulating in plasma at low concentrations have emerged as biomarkers of atherosclerotic risk. The aim of the present study is that of evaluating, in an athero‐prone mouse model, how different diets can affect plasma and aorta lipidome. Methods and results: Thirty‐six apoE knockout mice are divided in three groups and feed 12 weeks with diets differing for cholesterol and fatty acid content. Atherosclerosis is measured at the aortic sinus and aorta. Lipids are quantified in plasma and aorta with mass spectrometry. The cholesterol content of the diets is the main driver of lipid accumulation in plasma and aorta. The fatty acid composition of the diets affects plasma levels both of essential (linoleic acid) and nonessential (myristic and arachidonic acid) ones. Lipidomics show a comparable distribution, in plasma and aorta, of the main lipid components of oxidized LDL, including cholesteryl esters and lysophosphatidylcholines. Interestingly, lactosylceramide, glucosyl/galactosylceramide, and individual ceramide species are found to accumulate in diseased aortic segments. Conclusion: Both the cholesterol and fatty acid content of the diets profoundly affect plasma lipidome. Aorta lipidome is likewise affected with the accumulation of specific lipids known as markers of atherosclerosis. Abstract : This study investigates, in atherosclerosis‐prone mice, how diets with different lipid contents can affect the amount and composition of lipids in plasma and atherosclerotic plaques. The study demonstrates that dietary cholesterol and fatty acid composition strongly affect plasma and aortic lipidome of mice. That should be carefully considered when running studies aimed at looking for lipid biomarkers of disease.